Investigate how Ethnocultural Nationalism is Constructed within the concept of Hindu Rashtra and its implications for Social Dynamics in Contemporary India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The three pillars of Hindutva (Hindu Ness) upon which this creative vision rests are a shared language, shared culture, and shared genealogy. This homogeneity narrative has been prevalent across all socioeconomic, cultural, and national lines for the better part of a century, despite fierce opposition. After more than 90 years of exclusivist discourse, this study seeks to delve into the Hindu Right's cultural politics, apparatuses, methodology of meaning and impact, and national character imagination. The notion of "Hindu Rashtra" has been the target of criticism from many academics and political figures who have pitted it against Islam and other religions; nonetheless, this position is unfounded and unrealistic. These kinds of thinking sprang out of the horrors that the Islamic authority of mediaeval India imposed, and they also emerged during the British period. In the nineteenth century, Hindutva arose as a political philosophy in India as a reaction to British colonization. Neo-Hinduism emerged as a reform and revivalist movement in direct defiance of British rule. The concept of a 'golden era' in Hinduism, when the Vedas were authored and transported to northern India, became crystallized during this period. While focusing on Hindu nationalism's ideological baggage and its roots, traditional etic studies overlook the movement's day-to-day operations. By tracking its lineage, we can see how its philosophies have developed and the goals and forces that drove them.